Radiomics Nomograms Based on Non‐enhanced MRI and Clinical Risk Factors for the Differentiation of Chondrosarcoma from Enchondroma. Issue 4 (5th May 2021) - Pan, Jielin; Zhang, Ke; Le, Hongbo; Jiang, Yunping; Li, Wenjuan; Geng, Yayuan; Li, Shaolin; Hong, Guobin
Abstract : Background: Differentiating chondrosarcoma from enchondroma using conventional MRI remains challenging. An effective method for accurate preoperative diagnosis could affect the management and prognosis of patients. Purpose: To validate and evaluate radiomics nomograms based on non‐enhanced MRI and clinical risk factors for the differentiation of chondrosarcoma from enchondroma. Study Type: Retrospective. Population: A total of 103 patients with pathologically confirmed chondrosarcoma ( n = 53) and enchondroma ( n = 50) were randomly divided into training ( n = 68) and validation ( n = 35) groups. Field Strength/Sequence: Axial non‐contrast‐enhanced T1‐weighted images (T1WI) and fat‐suppressed T2‐weighted images (T2WI‐FS) were acquired at 3.0 T. Assessment: Clinical risk factors (sex, age, and tumor location) and diagnosis assessment based on morphologic MRI by three radiologists were recorded. Three radiomics signatures were established based on the T1WI, T2WI‐FS, and T1WI + T2WI‐FS sequences. Three clinical radiomics nomograms were developed based on the clinical risk factors and three radiomics signatures. Statistical Tests: The area under the receiver operating characteristic curve (AUC) was used to evaluate the performance of radiomics signatures and clinical radiomics nomograms. Results: Tumor location was an important clinical risk factor ( P < 0.05). The radiomics signature based on T1WI and T1WI + T2WI‐FS features performed better than that based on T2WI‐FS in the validation group (AUC in the validation group: 0.961, 0.938, and 0.833, respectively; P < 0.05). In the validation group, the three clinical radiomics nomograms (T1WI, T2WI‐FS, and T1WI + T2WI‐FS) achieved AUCs of 0.938, 0.935, and 0.954, respectively. In all patients, the clinical radiomics nomogram based on T2WI‐FS (AUC = 0.967) performed better than that based on T2WI‐FS (AUC = 0.901, P < 0.05). Data Conclusion: The proposed clinical radiomics nomogram showed promising performance in differentiating chondrosarcoma from enchondroma. Level of Evidence: 4 Technical Efficacy: Stage 2